MEM vs. FEM: practical crashworthiness insights for macro element modelling applied to sub-assembly and full vehicle automotive structures. Issue 6 (2nd November 2022) - Hughes, Kevin; Ramos, João; Vignjevic, Rade; Krzywobłocki, Marek; Djordjevic, Nenad; Campbell, James
Abstract: This paper proposes a modelling approach for integral vehicle structures, applied to frontal crash loading, based on the Macro element approach. Addressing the idealisation of complex sub-structures and full vehicle was through identification of critical parameters for conversion of validated FEM into MEM equivalents through sensitivity analyses. Two examples of impact onto rigid barriers are presented; 1). Frontal crash energy management system (consisting crush-can and longitudinal engine rail), impacting at 8.6 m/s and 2). A complete vehicle impact at 56 km/hr (15m/s). Both case studies predict key features of collapse, with force-time histories agreeing within ±10–15% against FEM. Case study 1 required a 3 second solution time versus 1.5 h (8CPUS) mass-scaled FEM (105k element). For Case study 2, MEM required 7.5mins versus 16.5 hrs for a 3 M element FEM vehicle. For all simulations, LS-DYNA R10.0 and Visual Crash Studio R4.0 used. Developing a framework to overcome accuracy/stability problems, together with issues related to robustness and error reduction is discussed. Model complexity was progressive, involving a-priori knowledge of collapse and/or analysing several sub-assemblies to guide idealisation. The level of agreement demonstrates the advantages of MEM as a complementary method to support conceptual vehicle design and offers significant advantages for design exploration, particularly across multiple crash certification cases. Highlights: Idealisation of complex sub-structures into Macro element modelling (MEM) equivalents using high fidelity finite element models (FEM) Methodology based on critical parameters for conversion of validated FEM into MEM Proposed MEM conversion for complete vehicle frontal impact onto a rigid barrier Correlation of critical parameters with structural behaviour through sensitivity analyses MEM error in force-time histories within 10–15%, relative to high fidelity FEM FEM Solution times reduced from several hours to several minutes for MEM equivalents